Mobile Computing and Security Issues - Odukale, Owodele (International Journal For Research In Advanced Computer Science And Engineering, 2015)
The past decade has seen a growth in the use of mobile computing. Its use can be found in areas such as social media, information exchange, online social gaming amongst others. However its use in the transmission of more sensitive data gives causes for concern due to its security vulnerabilities. Traditional computing systems make use of certain detection technologies and firewalls to prevent intrusion but such methods are difficult to apply with mobile computing thus making the security of data between mobile workstations and mobile unit a challenge. Challenges experienced in mobile communication include: forced de-authentication, disconnection and mimicry of the host mobile station or unit. The purpose of this research is to propose a secure mobile communication scheme that makes use of an asymmetric algorithm to encode the messages before transmission so as to provide secure communication over the channel. The mobile client will have a public key and a private key that will be used to encode messages sent over the communication channel while the server side decrypts the message using the private key.